The Effect of Delivery Services and Service Quality on Consumer Trust in Tiktok Online Stores - Alamsyah, Sal Sabila; Syahnur Aida Alifia; Ahmad Nuh (Penerbit Hellow Pustaka, 2024)
Online stores have become one of the most important aspects in the world of e-commerce, with increasing attention to factors that affect customer confidence in online transactions. The study aims to investigate the impact of service quality and customer satisfaction on customer confidence in the TikTok online store. The method used involves the use of online surveys using data filling forms (Google Forms) to users of the online shop. The data collected is analyzed using regression analysis to evaluate the relationship between independent variables (service quality and client satisfaction) and dependent variables. (customer trust). The results show that good service quality and customer satisfaction levels positively affect the level of customer confidence in TikTok online stores. These findings show the importance of providing high-quality service and paying attention to customers’ satisfaction to build trust in an e-commerce environment. The uniqueness of the study is the use of online surveys with data filling forms, which enables efficient data collection that can reach respondents from a variety of geographical backgrounds, as well as focusing on TikTok's still relatively new online shopping platform in the e-commerce market, adding insight into factors affecting customer confidence.